2014
DOI: 10.1021/pr500916m
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Ecotoxicoproteomics ofDaphnia pulex: Biochemical Effects of the Anticancer Drug Tamoxifen

Abstract: Among pollutants released into the environment by human activities, residues of pharmaceuticals are an increasing matter of concern because of their potential impact on ecosystems. The aim of this study was to analyze differences of protein expression resulting from acute (2 days) and middle-term (7 days) exposure of aquatic microcrustacean Daphnia pulex to the anticancer drug tamoxifen. Using a liquid chromatography-mass spectrometry shotgun approach, about 4000 proteins could be identified, providing the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Despite previous reports that quantitative proteomics in Daphnia presents significant challenges, we were able to obtain a deeper coverage of the proteins expressed across very different states of life cycle and conditions, using our standard proteomic sample preparation protocols and analysis procedures and identifying over 5000 proteins. The only previous study that was similarly successful in identifying individual D. pulex proteins utilized the label‐free MS protocol. There is a well‐established tradeoff between the depth of coverage and accuracy of quantitation when comparing label‐free and labeled MS proteomics analysis with that label free protocol allowing deeper coverage given the same running time per sample, but has a significantly higher variance among samples .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite previous reports that quantitative proteomics in Daphnia presents significant challenges, we were able to obtain a deeper coverage of the proteins expressed across very different states of life cycle and conditions, using our standard proteomic sample preparation protocols and analysis procedures and identifying over 5000 proteins. The only previous study that was similarly successful in identifying individual D. pulex proteins utilized the label‐free MS protocol. There is a well‐established tradeoff between the depth of coverage and accuracy of quantitation when comparing label‐free and labeled MS proteomics analysis with that label free protocol allowing deeper coverage given the same running time per sample, but has a significantly higher variance among samples .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report proteome differences between parthenogenetically produced embryos, juveniles, adults, and sexually produced resting eggs that can be used as a base‐line reference for protein expression analysis across the life cycle of an organism. Previous advances in Daphnia proteomics identified difficulties in obtaining a large number of intact and identifiable proteins due to high protease activity in tissue extracts, often resulting in a relatively small number of proteins reported (often 500–1500 out of over 25 000 predicted protein coding genes; the highest number reported close to 4000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultures of D. pulex were allowed to acclimatize to these conditions for a minimum of four generations prior to harvesting. Approximately 50 adult females were placed in algae free media for 12-14 h, filtered using ultra-soft [3] and Colbourne et al [1] C) Venn diagrams comparing proteins identified from proteomic analysis employing in-gel digestion (Gel), in-solution digestion (Soln), data-independent acquisition (MS E ), and/or MS E with ion mobility separation (HDMS E ). nylon mesh, frozen immediately in liquid nitrogen, and stored at −80°C.…”
Section: Doi: 101002/pmic201700460mentioning
confidence: 99%